2021
DOI: 10.1371/journal.pone.0253525
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracy of pleural fluid unstimulated interferon-gamma and adenosine deaminase for diagnosing pleural tuberculosis: A systematic review and meta-analysis

Abstract: Objective We compared diagnostic accuracy of pleural fluid adenosine deaminase (ADA) and interferon-gamma (IFN-γ) in diagnosing tuberculous pleural effusion (TPE) through systematic review and comparative meta-analysis. Methods We queried PubMed and Embase databases to identify studies providing paired data for sensitivity and specificity of both pleural fluid ADA and IFN-γ for diagnosing TPE. We used hierarchical summary receiver operating characteristic (HSROC) plots and HSROC meta-regression to model indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
1
8
2
Order By: Relevance
“…Studies in the same setting showed that ADA suffered from a sub-optimal specificity at a cut point of 30 IU/litre. In these settings, ADA specificity ranged from ~75% to 90% (6,10,18,23,24). This leads to false positives (in those without TB) and unnecessary initiation of treatment, which contributed to IRISA-TB being more cost effective compared to ADA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the same setting showed that ADA suffered from a sub-optimal specificity at a cut point of 30 IU/litre. In these settings, ADA specificity ranged from ~75% to 90% (6,10,18,23,24). This leads to false positives (in those without TB) and unnecessary initiation of treatment, which contributed to IRISA-TB being more cost effective compared to ADA.…”
Section: Discussionmentioning
confidence: 99%
“…IRISA-TB was found to be more cost-effective than ADA despite both tests having high sensitivity. Compared to ADA, several studies have shown that unstimulated IFNγ-based assays (including IRISA-TB) has a higher specificity and negative predictive value (6,11,18,22). Studies in the same setting showed that ADA suffered from a sub-optimal specificity at a cut point of 30 IU/litre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies usually adopt 35 U/L as a threshold for TPE diagnosis [ 12 , 15 ], which was also endorsed by the guideline [ 17 ]. Therefore, we used this threshold to determine the sensitivity and specificity of ADA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine deaminase (ADA) is the most studied among all available PF biomarkers. According to the published meta-analyses, PF ADA has a sensitivity of 90% and specificity of 92% [ 15 , 16 ]. Although PF ADA is not the gold standard test for the diagnosis of TPE, it is recommended as a ‘rule out’ test in countries with a low prevalence of TB, according to the British Thoracic Society Pleural Disease Guideline [ 17 ].…”
Section: Introductionmentioning
confidence: 99%